The Evolutionary Origins of the Wealth of Nations - Quamrul H. Ashraf; Oded Galor; Marc P. B. Klemp (Center for Economic Studies and Ifo Institute (CESifo), 2020)
This essay explores the deepest roots of comparative economic development. It underscores the significance of evolutionary processes since the Neolithic Revolution in shaping a society's endowment of fundamental traits, such as predisposition towards child quality, time preference, loss aversion, and entrepreneurial spirit, that have contributed to differential paths of technological progress, human-capital formation, and economic development across societies. Moreover, it highlights the indelible mark of the exodus of Homo sapiens from Africa tens of thousands of years ago on the degree of interpersonal population diversity across the globe and examines the impact of this variation in diversity for comparative economic, cultural, and institutional development across countries, regions, and ethnic groups.
Keywords: O11; N10; N30; Z10; 330; comparative development; human evolution; natural selection; preference for child quality; time preference; loss aversion; entrepreneurial spirit; the "out of Africa" hypothesis; interpersonal diversity